2020
DOI: 10.17305/bjbms.2020.5142
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene inhibits the overexpression of TGF-β1 in cartilage and regulates the metabolism of subchondral bone in rats with osteoporotic osteoarthritis

Abstract: Overexpression of transforming growth factor-beta 1 (TGF-β1) and subchondral bone remodelling play key roles in osteoarthritis (OA). Raloxifene (RAL) reduces the serum level of TGF-β1 in postmenopausal women. However, the effect of RAL on TGF-β1 expression in articular cartilage is still unclear. Therefore, we aimed to investigate the protective effect of RAL on osteoporotic osteoarthritis via affecting TGF-β1 expression in cartilage and the metabolism of subchondral bone. Osteoporotic osteoarthritis was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In our study, coexisting postmenopausal OP in OA rats accelerated the progression of OA pathology. Previous reports also showed that subchondral bone loss induced by OVX accelerated the progression of OA pathology in rodents 21 , 29 , 36 , 37 and rabbits 19 . However, rats with postmenopausal OP alone only echibited a reduction in safranin O staining in the superficial layer of articular cartilage.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, coexisting postmenopausal OP in OA rats accelerated the progression of OA pathology. Previous reports also showed that subchondral bone loss induced by OVX accelerated the progression of OA pathology in rodents 21 , 29 , 36 , 37 and rabbits 19 . However, rats with postmenopausal OP alone only echibited a reduction in safranin O staining in the superficial layer of articular cartilage.…”
Section: Discussionmentioning
confidence: 72%
“…Equol exhibits the highest estrogenic activity among all isoflavones and their metabolites [25]. Recent studies have shown that equol enhances osteoblastic bone formation, prevents bone loss, and protects cartilage and subchondral bone, demonstrating its bone-health properties [26,27]. Additionally, inverse relationships between equol production and various vascular pathologies, including cognitive impairment and dementia, have been observed [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that inhibition of TGF-β1 may have chondroprotective and regenerative effects in OA of human and rodents (24,26,35). Considering this potential efficacy, intra-articular injection materials that inhibit TGF-β1 have been used in canine OA, but the clinical evidence is still insufficient.…”
Section: Introductionmentioning
confidence: 99%